Inadmissible evidence - Friedman, Philip, 1944- (New York : Ivy Books, 1993)
"For tough New York City prosecutor Joe Estrada, the law is his life. That's why he's determined to get the goods on millionaire real-estate tycoon and community hero Roberto Morales, who is accused of raping and murdering his mistress. The more Joe investigates, however, the closer he moves to the possibility that Morales is innocent and that all he has to go on is...inadmissible evidence."--Cover.
National College of Business and Arts
Keywords: Evidence (Law) -- Fiction; Detective and mystery fiction